(untitled) (Religious dialogue and cooperation, 2023)
Following the idea of the famous Croatian sociologist Željko Mardešić (Jakov Jukić), this paper analyzes Mardešić’s vision of Christian dialogue and cooperation in the context of contemporary sociology of religion. The presented vision of dialogue and cooperation in relation to various social, cultural, and religious changes calls for expanding the space for dialogue and cooperation. According to Mardešić, dialogue and cooperation presuppose the existence of opposite ideas and not necessarily identity; otherwise, they would be reduced to mere confirmation. Thus, dialogue and cooperation observed separately contain an entire program and are key to the realization of Christianity in the future. Željko Mardešić sees the future of Christianity along the lines of the Second Vatican Council, which remains the “compass” for the Catholic Church, on four council levels: establishing a dialogue with divided Christians, major world religions, non-believers, and the modern world. Importantly, dialogue and cooperation in the Church represent an unavoidable prerequisite to establishing four effective dialogues with the world. In this context, the authenticity of Christian dialogue and cooperation, according to Željko Mardešić, can be summed up in a few demanding words: kindness, forgiveness, mercy, service, peace, and the joy of hope. A person – not seen as an object but a subject of experience – is certainly changed by every dialogue because the experience itself is dialogical and open to cooperation.